To the limit : the essential collection [compact disc] (Warner Music Group, 2023)
This collection thoughtfully curates 51 songs from the studio albums and live recordings the Eagles released between 1972 and 2020. All of the band's best-known tracks are here, including the number one hits New Kid in Town; One of These Nights; and Hotel California.